Transient expression of the enhanced green fluorescence protein (egfp) gene in Tetraselmis subcordiformis (Chlorodendrales, Chlorophyta) with three exogenous promoters. Issue 5 (1st September 2016) - Cui, Yulin; Qu, Lin; Zhao, Jialin; Qin, Song
Abstract: A stable transformation system for Tetraselmis subcordiformis had been established, but a low transformation rate limits its application to this alga. As a promoter is a key factor for transgenic research, a suitable promoter could increase the transformation rate. To improve a transformation system for T. subcordiformis, three commonly used promoters for algal transformation were selected. The CMV, CaMV35S and SV40 promoters were transferred to T. subcordiformis by glass-bead agitation and particle bombardment, with the enhanced green fluorescence protein (e gfp ) gene as the reporter gene. The transformation rate was calculated according to the GFP fluorescence in transformed algae. Results showed that the CaMV 35S promoter transformation efficiency was higher than that of CMV and SV40 promoters. This report will contribute to efforts to establish a high-efficiency transformation system and expands the fundamental research and applications of this alga.